Comparison of parenteral iron sucrose and oral iron preparations in the treatment of postpartum anemia at tertiary health care centre: randomised controlled trial study - Sirsam, Shyamkumar S.; Patil, Bhupendra V.; Sanap, Mangesh B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Postpartum anemia is a leading cause of maternal morbidity and delayed recovery after childbirth. Oral iron therapy, though widely used, is often limited by gastrointestinal side effects and poor absorption. This study compared the efficacy and safety of intravenous (i.v.) iron sucrose versus oral iron in treating postpartum anemia. Methods: A randomized controlled trial was conducted in the department of obstetrics and gynecology, Government Medical College, Akola, Maharashtra. A total of 108 postpartum women with iron deficiency anemia were randomly assigned to two groups. Group A received i.v. iron sucrose (200 mg on alternate days, total 1000 mg) and group B received oral ferrous sulphate (325 mg thrice daily) for six weeks. Hemoglobin (Hb) and serum ferritin were measured at baseline, four, and six weeks. Adverse drug reactions (ADRs) and treatment efficacy (Hb rise >3.5 gm/dl) were analysed statistically. Results: Both groups were comparable at baseline. Mean Hb rise was significantly higher with i.v. iron (3.8±0.6 gm/dl at 4 weeks; 4.2±0.7 gm/dl at 6 weeks) than with oral iron (2.9±0.7 and 3.3±0.6 gm/dl; p<0.001). Serum ferritin increased more with i.v. iron (95.4 ng/ml versus 71.1 ng/ml; p<0.001). ADRs were fewer in the i.v. group (14.8%) than in the oral group (40.7%; p<0.001). Conclusions: Intravenous iron sucrose is a safe, well-tolerated, and more effective alternative to oral iron for rapid correction of postpartum anemia.